2023
DOI: 10.3390/ijerph20010890
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spatial Accessibility of Community Hospitals for the Elderly in Beijing, China

Abstract: Accessibility of health services signifies the quality and equitability of universal health provision. The hierarchical medical system recently implemented in China offers the policy instruments to improve medical services to the elderly in an aging society. As the critical primary care gateway, accessibility to community hospitals has significant impacts on people’s health. However, current research has paid little attention to spatial accessibility within walking distance of community hospitals, especially f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Based on the above inference, we searched parallel literature and found that most studies that have explored the gap in healthcare between potential access (supply) and realized access (utilization) focus on a large scale (city, county, or village scale) (31)(32)(33). In China, the restricting factor could be linked to the uncompleted constructed database at the community level and undisclosed information of CHCs (private or publicprivate partnership).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above inference, we searched parallel literature and found that most studies that have explored the gap in healthcare between potential access (supply) and realized access (utilization) focus on a large scale (city, county, or village scale) (31)(32)(33). In China, the restricting factor could be linked to the uncompleted constructed database at the community level and undisclosed information of CHCs (private or publicprivate partnership).…”
Section: Introductionmentioning
confidence: 99%
“…H-H matching spaces located in central areas have a concentrated elderly population and relatively abundant medical facilities. However, L-L matching spaces in the suburbs have a smaller population, especially for the elderly population, and relatively scarce facilities [44,46,50,51]. Additionally, the number of L-L spatial units is 1.5 times that of H-H spatial units, which is closely related to the expansion model being implemented in the central area with limited land resources and the conversion of large amounts of agricultural land to suburban development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the "integration of medical treatment and elderly support" reform promotes the embedding of medical and health services into the community and institutional care for the elderly [ 12 ]. Recent reforms in public hospitals and the construction of a hierarchical healthcare system have provided a strong impetus for the development of senior healthcare [ 13 ]. To a certain extent, these reforms have the potential to mitigate the the healthcare demands of the ageing population, enhance the prioritization of elderly patients, and optimize the utilization of medical resources for the elderly.…”
Section: Introductionmentioning
confidence: 99%